Different Temporal Patterns of Specific and General Autobiographical Memories across the Lifespan in Alzheimer’s Disease - Nathalie Philippi; François Rousseau; Vincent Noblet; Anne Botzung; Olivier Després; Benjamin Cretin; Stéphane Kremer; Frédéric Blanc; Liliann Manning (Behavioural Neurology)
We compared specific (i.e., associated with a unique time and space) and general (i.e., extended or repeated events) autobiographical memories (AbM) in Alzheimer’s disease (AD). The comparison aims at investigating the relationship between these two components of AbM across the lifespan and the volume of cerebral regions of interest within the temporal lobe. We hypothesized that the ability to elicit specific memories would correlate with hippocampal volume, whereas evoking general memories would be related to lateral temporal lobe. AbM was assessed using the modified Crovitz test in 18 patients with early AD and 18 matched controls. The proportions of total memories—supposed to reflect the ability to produce general memories—and specific memories retrieved were compared between AD patients and controls. Correlations to MRI volumes of temporal cortex were tested. We found different temporal patterns for specific and general memories in AD patients, with (i) relatively spared general memories, according to a temporal gradient that preserved remote memories, predominantly associated with right lateral temporal cortex volume. (ii) Conversely, the retrieval of specific AbMs was impaired for all life periods and correlated with bilateral hippocampal volumes. Our results highlight a shift from an initially episodic to a semantic nature of AbMs during AD, where the abstracted form of memories remains.